Data Mining Pengelompokan Pasien Rawat Inap Peserta BPJS Menggunakan Metode Clustering (Studi Kasus : RSU.Bangkatan) - Novi Karolina Surbakti (Department of Information Technology, Universitas Timor, Indonesia, 2021)
The system currently used by the hospital is still manual in managing patient data and information, therefore it is necessary to have a Bangkat Binjai Hospital Service system to provide complete and detailed information to hospital patients using BPJS. So in this case the author will design and build a system that will be used in grouping inpatients based on the BPJS Class and the variables determined using the clustering method, so that later it can make it easier for administrators to process data and information on inpatients using BPJS. From the tests carried out using the clustering method with the k-means algorithm, it can be seen that cluster 3 of the criteria for disease type, diagnosis result, and age, the group that has the highest set / value of BPJS Class patient data, namely in Cluster 1 totaling 435 patient data Inpatients using BPJS at the age of 20-39 years and the type of disease are benign tumors, then the BPJS class used is the Level 2 BPJS. Inpatients who use BPJS at the age of 20-39 years and the type of disease is heart complications, then the BPJS class used is BPJS Level 1. And the group that has the highest set / value of BPJS Class patient data, namely Cluster 3 totaling 270 inpatient data. who used BPJS at the age of 20-39 years and the type of disease was uric acid, then the BPJS class was used is BPJS Level 1.